Community structure of soil microarthropods in active and passive zones of Ngronggo landfill Salatiga - Psn Masruri Sulistiyanto Ari; Rully Rahadian; Udi Tarwotjo (Department of Biology, Faculty of Sciences and Mathematics, Universitas Diponegoro, 2019)
Soil microarthropods play a key role in decomposing organic materials. The objectives of this study were to compare the structure of soil microarthropods communities in the active and passive zones of Ngronggo landfill Salatiga. The sampling of ten soil samples in each active and passive zones was performed for soil microarthropods extraction and soil physical-chemical analysis. Soil microarthropods were extracted using modified Barlese-Funnel. Soil microarthropods data were analyzed to determine abundance, diversity, and similarity. Physical-chemical factors were measured, including soil texture, heavy metal content (Pb, Cd, Cu, Zn, and Hg) and organic matter. The results show that all attributes of structure of soil microarthropods communities in active zone are higher than in passive zone, i.e., the density, the species richness, the species diversity, and the evenness. In both zones, the composition of soil microarthropods tend to be different.. Organic matter is likely the most important soil physicochemical factors to form the microarthropod structure in active and passive zones. This study contributes a new information about the role of soil microarthropods in decomposing the disposal waste of material and it would be benefit for developing a bioindicator of waste decomposition in landfill area.